Infiltration-driven performance enhancement of poly-crystalline cathodes in all-solid-state batteries - Junghwan Sung; Junyoung Heo; Dong-Hee Kim; Hawon Gu; Yung-Soo Jo; Heetaek Park; Jun-Ho Park; Jeong-Hee Choi; Yoon-Cheol Ha; Doohun Kim; Jun-Woo Park (NPG Asia Materials)
Abstract All-solid-state batteries (ASSBs) with adequately selected cathode materials exhibit a higher energy density and better safety than conventional lithium-ion batteries (LIBs). Ni-rich layered cathodes are benchmark materials for traditional LIBs owing to their high energy density. Recent studies have highlighted the advantages of using crack-free, single-crystalline cathode materials in ASSBs. In this study, a scalable infiltration sheet-type process was used to fabricate composite electrodes with different cathode-material morphologies for ASSBs. Typically, crack-free single-crystalline materials exhibit better retention performance and lower rate capability (i.e., slower kinetics in charge‒discharge processes) than polycrystalline cathode materials. Li6PS5Cl-infiltrated polycrystalline electrodes showed excellent retention performance and rate capability. Galvanostatic intermittent titration technique analysis and transmission electron microscopy of the single-crystalline electrode confirmed severe polarization and the presence of a rock-salt-structure layer in the cathode particles; these results indicated side reactions within the layered structure of the material. In contrast, composite electrodes consisting of polycrystalline cathode materials infiltrated with the solid electrolyte Li6PS5Cl showed excellent electrochemical performance owing to intimate electrode–electrolyte interfacial contact. The result from this study confirmed the critical influence of interface engineering and material morphology on the overall performance and stability of ASSBs and could facilitate the development of high-performance ASSBs in the future.